2019
DOI: 10.4236/as.2019.107064
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Acidity of a Brazilian Cerrado Oxisol with Limestone and Wood Ash on the Initial Growth of Cowpea

Abstract: Among Brazilian soils orders, there are some of it classified as acid soils, which need correction to guarantee crop productivity. Currently, limestone is the most used soil corrective and wood ash has been a sustainable alternative to this process. Thus, the objective was to evaluate the effect of two correctives of soil acidity on an Oxisol collected in the Brazilian Cerrado area using limestone and wood ash and the effect of soil correction on initial growth of cowpea. Two greenhouse experiments were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…While nutrient demand indicates a plant's nutrient needs, the supply of nutrients is based on the availability of mineral nutrients from the soil, which is influenced by the soil acidity (pH), texture, water availability, plant root density, and nutrient leaching. While some of these factors generally stay constant, others show seasonal patterns based on a specific location [43,45]. Due to these uncertainties, it is very complicated for the oil palm estate to develop a standard fertilization routine for best sustainable soil management practices, ensuring efficiency, effectiveness, and high yield [2].…”
Section: Soil Management Practices In Oil Palm Plantationmentioning
confidence: 99%
See 1 more Smart Citation
“…While nutrient demand indicates a plant's nutrient needs, the supply of nutrients is based on the availability of mineral nutrients from the soil, which is influenced by the soil acidity (pH), texture, water availability, plant root density, and nutrient leaching. While some of these factors generally stay constant, others show seasonal patterns based on a specific location [43,45]. Due to these uncertainties, it is very complicated for the oil palm estate to develop a standard fertilization routine for best sustainable soil management practices, ensuring efficiency, effectiveness, and high yield [2].…”
Section: Soil Management Practices In Oil Palm Plantationmentioning
confidence: 99%
“…Soil pH is known to influence a variety of soil characteristics needed by plants for healthy growth and development (e.g., resistance against diseases, root system, soil microbial activities, availability of nutrients, and rate of photosynthesis), resulting in projected harvests [10,11,45]. Soil acidification processes can be classified into two major categories: (i) by natural causes (e.g., rainfall, nutrients leaching, and decomposition of organic materials) and (ii) by controlled agro-ecosystem through excessive agricultural operations (e.g., application of N-fertilizers and harvest of high-yielding crops) [15].…”
Section: Neutralizing Soil Aciditymentioning
confidence: 99%
“…The use of liming raises the soil pH and base saturation (Rouphael et al, 2016;Zhou et al, 2020) besides releasing calcium (Ca) and magnesium (Mg) into the soil (Moreira, Prochnow, et al, 2017;Neto Mesper, Coneglian, Costa, Inoue, & Batista, 2019;Zhou et al, 2020). The increase in pH has a direct influence on the reduction of Al toxicity and increase of base saturation and hence can change the availability of nutrients in the soil for plants (Bonfim-Silva et al, 2019;Horst, Asher, Cakmak, Szulkiewicz, & Wissemeier, 1992;Miranda & Miranda, 2000). The limestone in adequate levels in the soil, besides releasing Ca and Mg, provides a greater availability of nutrients for plant growth.…”
mentioning
confidence: 99%
“…Ajala et al (2019), report that wood ash increased the yield of maize and lima beans. Bonfim-Silva et al (2019) showed that wood ash increased the pH of the soil to adequate values and made K available, resulting in better initial development of cowpea and Bhutia et al (2019) find excellent yields for growing peas.…”
Section: Introductionmentioning
confidence: 99%